Etiologies and Outcomes of Acute Liver Failure in a Spanish Community - Emilio Fábrega; Miguel Ángel Mieses; Alvaro Terán; Irene Moraleja; Fernando Casafont; Javier Crespo; Fernando Pons-Romero (International Journal of Hepatology)
Previous retrospective study (1992 to 2000) performed in Spain showed that drug toxicity, viral hepatitis, and indeterminate etiology were the most prevalent causes of acute liver failure (ALF). In the last decade, there is no information about ALF in our country. For these reasons we analyze retrospectively, in a ten-year period (2000 to 2010), the presumed causes, clinical characteristics, course, and outcome of ALF in a Spanish community. Causes of ALF were indeterminate in 4 patients (24%), acute hepatitis B infection in 4 patients (24%), drug or toxic reactions in 4 patients (24%), including one case of acetaminophen overdose, followed by miscellaneous causes. The overall short-term survival (6 weeks after admission) was 65%. Liver transplantation was performed in 11 patients with a survival of 82%. Despite fulfilling criteria, 2 patients were not transplanted because of contraindications; they both died. In summary, acute hepatitis B and indeterminate cause are still being the most frequent causes of ALF in our region, and patients with ALF have an excellent chance of survival after emergency liver transplantation. Acetaminophen overdose still represents a very rare cause of ALF in our community.